The mental health impact of multiple deprivations under protracted conflict: A multi-level study in the occupied Palestinian territory. - Weeam Hammoudeh; Suzan Mitwalli; Rawan Kafri; Tracy Kuo Lin; Rita Giacaman; Tiziana Leone (Public Library of Science (PLoS), 2022)
Building on the literatures examining the impacts of deprivation and war and conflict on mental health, in this study, we investigate the impact of different forms of deprivation on mental health within a context of prolonged conflict in the occupied Palestinian territory(oPt). We expand the operationalization go deprivation while accounting for more acute exposures to conflict and political violence and spatial variations. We use multilevel modelling of data from the Socio-Economic & Food Security Survey 2014 conducted by the Palestinian Central Bureau of Statistics, which included a sample size of 7827 households in the West Bank(WB) and Gaza Strip(GS). We conduct the analysis for the combined sample, as for the WB and GS separately. We use a General Health Questionnaire-12 (GHQ12) score as our main outcome measure of poor health. We used various measures of deprivation including subjective deprivation, material deprivation, food deprivation, and political deprivation. In addition to the different measures of deprivation, we included acute political, health, and economic shocks in our analysis along with background socio-demographic characteristics. The results indicate significant variance at the locality level. We find a significant association between poor mental health and subjective, economic, political, and food deprivation; health, economic, and political stressors; age, and being a woman. Post-secondary education and wealth have a significant inverse association with poor mental health. Subjective deprivation is the strongest predictor of GHQ12 score in the models whereby people who feel very deprived have GHQ12 scores that are almost 4-points higher than people who do not feel deprived. Economic conditions, particularly subjective measures, are significant predictors of mental health status. Our findings confirm that political and social factors are determinants of health. Feeling deprived is an important determinant of mental health. The community effect suggests that spatial characteristics are influencing mental health, and warrant further investigation.